2018
DOI: 10.1080/17565529.2018.1521330
|View full text |Cite
|
Sign up to set email alerts
|

International trade and the distribution of economy-wide benefits from the disbursement of climate finance

Abstract: In the framework of recent international climate negotiations, industrialised countries have committed to transfer at least USD 100 billion per year to developing countries from 2020. Climate finance has become the subject of an already extensive literature. However, the economic impact of the disbursement of climate finance and the role of international trade in its distribution globally have not been studied yet. This paper specifically estimates the geographical distribution of economic benefits for 17 miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Spill-overs, in particular, have been analysed in the study of the crossborder effects of trade (Arto et al, 2015). In the field of climate policy, the recent papers by Markandya et al (2016) and Román et al (2018b) track the domestic and cross-border effects (on employment and value added, respectively) associated to the energy transition in the EU in the former, and to climate finance disbursements in the latter. For this exercise, the World Input-Output Database (WIOD) is used.…”
Section: Methods and Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Spill-overs, in particular, have been analysed in the study of the crossborder effects of trade (Arto et al, 2015). In the field of climate policy, the recent papers by Markandya et al (2016) and Román et al (2018b) track the domestic and cross-border effects (on employment and value added, respectively) associated to the energy transition in the EU in the former, and to climate finance disbursements in the latter. For this exercise, the World Input-Output Database (WIOD) is used.…”
Section: Methods and Datamentioning
confidence: 99%
“…It can be expected that international climate finance flows will continue to grow in the near future, so it is important to understand the economic consequences of these flows. The study of the geographic distribution of the economic impact of climate finance shows that, while the largest share of the impact is local, international trade deviates one part of the impact away from the recipient country (Román et al, 2018a(Román et al, , 2018b. This part constitutes the so-called spill-over effect ii .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, research on the mechanisms of domestic and international climate finance policies are on the rise. For instance, some previous studies have investigated the influence of bureaucratic agencies on climate finance allocation (Peterson & Skovgaard, 2019), coastal adaption project design patterns and contributions (Kuhl et al, 2020), economic impacts of climate actions between countries (Román et al, 2019), climate mainstreaming (Bhandary, 2021), the complementarity or disparity between domestic and international climate policies (Peterson, 2021), the impact of self-regulation in the adoption of the Equator Principles (Contreras et al, 2019), and the moderating role of politics and the media in climate investment decisions (Bae et al, 2021;Pickering & Mitchell, 2017). It is observed that past studies have focused on the barriers, strategies, and the impact of climate finance at both domestic and international levels.…”
Section: Domestic and International Climate Finance Policiesmentioning
confidence: 99%